'There is another story': writing after the Odyssey in Margaret Atwood's The Penelopiad. (14th December 2017) - Hauser, Emily
Abstract: In this article, I explore how Margaret Atwood's The Penelopiad (2005) provides a retrospective vision of an Odyssey that has already happened — and, by so doing, opens up an extended investigation of what it means to receive the texts and myths of the classical past. By responding to and reformulating the tale of the Odyssey after the event, Penelope's storytelling mirrors the process of reception — what James Porter has called a 'retrospective' form of reception, where the classical is 'identifiable only après coup ' (2006: 53). But I also suggest that there is a second layer to Atwood's allegorizing of classical reception in The Penelopiad : one which, by consciously correcting the narrative of the Odyssey via the subversive counterstory of the maids, showcases a vision of reception as retelling and complicating classical texts, both by inserting a new (and often subversive) narrative, and by emending the multiform text of the Odyssey to the 'correct' edition. The Penelopiad thus becomes an exploration of what it means to interpret narratives within the classical tradition — suggesting that we are not only respondents to, but also, like the maids, direct participants in the classical past.